2020
DOI: 10.1080/22221751.2020.1837018
|View full text |Cite
|
Sign up to set email alerts
|

Viral RNA level, serum antibody responses, and transmission risk in recovered COVID-19 patients with recurrent positive SARS-CoV-2 RNA test results: a population-based observational cohort study

Abstract: (2020): Viral RNA level, serum antibody responses, and transmission risk in recovered COVID-19 patients with recurrent positive SARS-CoV-2 RNA test results: a population-based observational cohort study, Emerging Microbes & Infections,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
69
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 19 publications
1
69
2
1
Order By: Relevance
“…The second one reported 119 discharged patients and 111 close contacts up till 23 April 2020 [ 11 ]. The last one reported 479 recovered COVID-19 patients and 96 close contacts from February 1 to May 5, 2020 [ 10 ]. The above reports were limited to a small group of people; the observation and follow-up times were not long enough.…”
Section: Discussionmentioning
confidence: 99%
“…The second one reported 119 discharged patients and 111 close contacts up till 23 April 2020 [ 11 ]. The last one reported 479 recovered COVID-19 patients and 96 close contacts from February 1 to May 5, 2020 [ 10 ]. The above reports were limited to a small group of people; the observation and follow-up times were not long enough.…”
Section: Discussionmentioning
confidence: 99%
“…Second, as the study population contains only Chinese participants, it may be not generalizable to other ethnic groups. Third, all controls (nonrecurrent positive) were followed up for only two months, and it was not clear whether they will return to positive after that, but the current study showed that most recurrent occur within 1 month, rarely more than two months [5,19]. Because of the small number of cases in the Age and underlying disease (Diabetes, chronic pulmonary disease, coronary heart disease, chronic kidney disease, chronic liver disease, malignant tumor) subgroups, it is failed to calculate the effect value, confidence interval and interaction P value Because 1 patient is chronic lymphoblastic leukemia, there are abnormal values at the maximum of white blood cell count, lymphocyte count and lymphocyte percentage CI confidence interval, OR odd ratio…”
Section: Discussionmentioning
confidence: 64%
“…4 Department of Tuberculosis, Wuhan Pulmonary Hospital, Wuhan, China. 5 Department of Infectious Disease, The First Affiliated Hospital of Chongqing Medical University, Chongqing, China. 6 Administrative Office, Chengdu Public Health Clinical Center, Chengdu, China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen (of 183 RT-PCR positive) study samples cultured for SARS-CoV-2 on VeroTMPRSS2 cells [16,25] from 14 participants were virus culture positive ( Figure 3A, red circles). In these 14 participants, the median time from symptom onset to last positive virus culture was 5 days (range [2][3][4][5][6][7][8][9][10][11]. No sample tested positive for virus culture beyond 11 days from symptom onset, even in the case of an immunocompromised participant who had positive RT-PCRs with low Ct values two months post-symptom onset ( Figure 3A).…”
Section: Resultsmentioning
confidence: 99%